A review of acoustic power transfer for bio-medical implants. (11th November 2016) - Basaeri, Hamid; Christensen, David B; Roundy, Shad
Abstract: Bio-implantable devices have been used to perform therapeutic functions such as drug delivery or diagnostic monitoring of physiological parameters. Proper operation of these devices depends on the continuous reliable supply of power. A battery, which is the conventional method to supply energy, is problematic in many of these devices as it limits the lifetime of the implant or dominates the size. In order to power implantable devices, power transfer techniques have been implemented as an attractive alternative to batteries and have received significant research interest in recent years. Acoustic waves are increasingly being investigated as a method for delivering power through human skin and the human body. Acoustic power transfer (APT) has some advantages over other powering techniques such as inductive power transfer and mid range RF power transmission. These advantages include lower absorption in tissue, shorter wavelength enabling smaller transducers, and higher power intensity threshold for safe operation. This paper will cover the basic physics and modeling of APT and will review the current state of acoustic (or ultrasonic) power transfer for biomedical implants. As the sensing and computational elements for biomedical implants are becoming very small, we devote particular attention to the scaling of acoustic and alternative power transfer techniques. Finally, we present current issues and challenges related to the implementation of this technique for powering implantable devices.